A Broadband Circularly Polarized Stacked Probe-Fed Patch Antenna for UHF RFID Applications - Hang Leong Chung; Xianming Qing; Zhi Ning Chen (International Journal of Antennas and Propagation)
A broadband circularly polarized stacked probe-fed antenna suitable for UHF RFID applications is presented and studied. The proposed antenna is fed by two probes which are connected to a hybrid coupler. Two parasitic patches are stacked above a primary probe-fed patch to enhance the bandwidth of the antenna. The optimized antenna prototype achieves gain of more than 6.5 dBic, axial ratio of less than 3.0 dB, and return loss of less than −15 dB over the UHF band of 820–980 MHz (17.7%). Parametric studies are carried out to demonstrate the effects of antenna geometry parameters on the performance. The proposed antenna can be a good candidate for UHF RFID applications.